Efficient stabilization of cyanonaphthalene by fast radiative cooling and implications for the resilience of small PAHs in interstellar clouds - Mark H. Stockett; James N. Bull; Henrik Cederquist; Suvasthika Indrajith; MingChao Ji; José E. Navarro Navarrete; Henning T. Schmidt; Henning Zettergren; Boxing Zhu (Nature Communications)
Abstract After decades of searching, astronomers have recently identified specific Polycyclic Aromatic Hydrocarbons (PAHs) in space. Remarkably, the observed abundance of cyanonaphthalene (CNN, C10H7CN) in the Taurus Molecular Cloud (TMC-1) is six orders of magnitude higher than expected from astrophysical modeling. Here, we report unimolecular dissociation and radiative cooling rate coefficients of the 1-CNN isomer in its cationic form. These results are based on measurements of the time-dependent neutral product emission rate and kinetic energy release distributions produced from an ensemble of internally excited 1-CNN+ studied in an environment similar to that in interstellar clouds. We find that Recurrent Fluorescence – radiative relaxation via thermally populated electronic excited states – efficiently stabilizes 1-CNN+, owing to a large enhancement of the electronic transition probability by vibronic coupling. Our results help explain the anomalous abundance of CNN in TMC-1 and challenge the widely accepted picture of rapid destruction of small PAHs in space.